Benzohydroxamic acid on rutile TiO2(110)-(1×1)– a comparison of ultrahigh-vacuum evaporation with deposition from solution - Köbl, Julia; Fernández, Cynthia C.; Augustin, Lisa-Marie; Kataev, Elmar; Franchi, Stefano; Tsud, Nataliya; Pistonesi, Carolina; Pronsato, M. Estela; Jux, Norbert; Lytken, Ole; Williams, Federico J.; Steinrück, Hans-Peter (Surface Science, 2022)
Hydroxamic acids are an interesting anchor group for organic molecules on oxide surfaces, but very few studies exist on their adsorption on well-defined single-crystal surfaces under well-defined conditions. In the present paper, we use X-ray photoelectron spectroscopy to follow the adsorption of benzohydroxamic acid on a rutile TiO2(110)-(1×1) single-crystal surface. We compare evaporation in ultrahigh vacuum with deposition from ethanol and acetonitrile solutions. Furthermore, we carried out density functional theory calculations to support the assignment of adsorbates. Several species appear on the surface, which are most evident in the N 1s region. The low-coverage species can be explained as originating from a hydroxamate, and decomposed species related to oxygen vacancies or defects. Identification of the high-coverage species, however, remains elusive, and several possibilities are discussed.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Benzohydroxamic acid; Density functional theory calculations; TiO; X-ray photoelectron spectroscopy (XPS)